Secular and Religious Humanism in Selected Pakistani English Fiction - Khan, Muhammad Arif; Shahid, Shahid Hussain (Annals of Human and Social Sciences, 2023)
Pakistani English fiction has since long been representing the dominant and peripheral currents of Pakistani society. With this background in view the main objective of this research is to investigate the presence of secular and religious humanism in selected Pakistani English fiction. Secularity and religiosity both appear to have coexisted here and this trend has not stopped yet. Some Pakistani writings which reflect secular and religious humanism include Ice – Candy – Man, Meatless Days, Moth Smoke, Holy Woman, The Geometry of God, and Home Boy. Narrative and thematic analysis is used for this research. The study finds that the scope of these two competing isms, because of national and international affairs, has been on the rise despite their progressive and regressive roles. It recommends that humanism in any of its forms, especially secular and religious, needs to be cautiously embedded in literary productions as both may have far reaching consequences for societal make up at home or abroad.